Attitudes Towards the Use of Robots in the Service Sector on Customer Satisfaction, Revisits and Recommendations Within the Perceived Innovativeness Framework - ERGAN, Senem; ERU, Oya; YAKIN, Volkan (International Journal of Contemporary Economics and Administrative Sciences, 2025)
With the rapid advancement of technology, the use of robots in the service sector is becoming increasingly widespread. This study examines how robot usage in the service sector affects customer satisfaction, revisit intention, and recommendations through the lens of perceived innovativeness. Data was collected using a survey method from 380 individuals who had received food and beverage services. The analysis results indicate that perceiving robots as innovative positively influences customer satisfaction. Furthermore, customers' attitudes toward robots in food and beverage services impact on their intention to recommend and revisit the restaurant. In conclusion, the use of robots in the service sector has the potential to enhance customer experience. To increase customer satisfaction, revisit intention, and positive recommendation behavior, businesses must emphasize the innovative features of robots.